Teacher Emotional Intelligence and Classroom Leadership Dynamics in Differentiated Learning - Hasrat A Aimang; Bernadette O Gallardo (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to examine the relationship between teachers’ emotional intelligence and classroom leadership dynamics in supporting the effectiveness of differentiated learning for students at Senrior high school Muhammadiyah Luwuk. Methodology: The research method used is a qualitative approach with a case study design. Data were collected through in-depth interviews, classroom observations, and documentation involving teachers, students, and school principals. Data were analyzed using reduction, display, and verification techniques to gain an in-depth understanding of classroom leadership practices and teachers’ emotional intelligence. Main Findings: The results show that teachers with high levels of emotional intelligence tend to be more adaptive in dealing with classroom dynamics and are able to create an inclusive and participatory learning environment. Dimensions such as empathy, self-awareness and the ability to manage emotions play an important role in facilitating learning differentiation. In addition, transformational leadership style is proven to be effective in building positive relationships between teachers and students, which has a direct impact on improving student motivation and learning outcomes. In conclusion, teachers' emotional intelligence and dynamic classroom leadership are key factors in the successful implementation of differentiated learning. Novelty/Originality of this study: These findings provide important implications for teacher professional development and more targeted training design. Previous studies have mostly focused on the individual effects of emotional intelligence or teacher leadership on learning outcomes, while the dynamic interaction between the two in shaping differentiated learning practices is still an open area for further exploration.